COVID-19: The catalyst for digital transformation in the hospitality industry? - Antonio, Nuno; NOVA IMS (2021)
Until the outbreak of COVID-19, digital transformation was not on many hotels' strategic plan, despite its efficiency-related benefits for saving time, creating better customer experiences, increasing revenue, and supporting decision-making. However, like in many other industries, the COVID-19 physical distancing good practices and governments' restrictions acted as a catalyst and promoted hotels' digitalization. To this end, a questionnaire was administered to 51 hotel managers to verify if that happened in Portuguese hotels and what processes were most impacted. Results showed that 92% of the hotel managers agreed that COVID-19 promoted the digitalization of processes, with most organizations considering that online meetings and technology productivity tools are here to stay. Hotels’ digitalization has the potential to generate high-efficiency gains both in public-facing operations as well as in back-office operations. This study highlights these implications and intends to spur researchers to investigate the practical impact of these implications on business efficiency and social theory.